Assessing Nurses Knowledge of Glasgow Coma Scale in Emergency and Outpatient Department - Basauhra Singh, H.K.; Chong, M.C.; Thambinayagam, H.C.; Zakaria, M.I.; Cheng, S.T.; Tang, L.Y.; Azahar, N.H. (Hindawi Publishing Corporation, 2016)
Assessment of level of consciousness using the Glasgow Coma Scale (GCS) is a tool requiring knowledge that is important in detecting early deterioration in a patient’s level of consciousness. Critical thinking used with the skill and knowledge in assessing the GCS is the foundation of all nursing practice. This study aims to explore the knowledge and competence in assessing the GCS among staff nurses working in the Emergency and Outpatient Departments. This is a quantitative descriptive cross-sectional study design using the GCS Knowledge Questionnaire. Convenience sampling method was used. Nurses in these Departments were asked to partake in the survey. Data collected was analyzed using the Statistical Package of Social Sciences (SPSS) version 20. Descriptive and Pearson’s chi square was used. Result showed that 55.56% of nurses had poor knowledge followed by 41.48% and 2.96% with satisfactory knowledge and good knowledge, respectively. The result on the association between knowledge and education level showed a significant association between the two variables (, df = 3, , and ). There was also a significant correlation between knowledge and age group (, df = 2, , and ). Overall, this study supports that good knowledge and skill are important in assessing GCS level.